Tugas Dan Wewenang Majelis Permusyawaratan Rakyat Republik Indonesia Menurut Uud Ri 1945 Perubahan/Amandemen - Rusnan - (Fakultas Hukum Universitas Mataram, 2011)
Before the reformation, the authority of People’s Advisory Assembly of Indonesia Republic (MPR-RI) given by the 1945 Constitution was so centered only to this institution, that there was not check and balance among the structures of state institution that enables for democracy. The reformation spirit, starts an effort to do restructuring in the state institutions, especially, MPR. It aims to minimize or limit the duty and authority of MPR in order to achieve democratic atmosphere and give the priority to checks and balances and to resume the people’s power fully to the people’s hand. This was based on the consideration that this research attempted to find out the norms and legal theory about the existence of MPR authority. according to the new the 1945 Constitution, MPR was changed from the highest state institution to be equal to the other state institutions (DPR, DPD, President, BPK, and the Institution of Justice, namely, MK MA, and KY). The MPR authority was limited in three main cases: changing and deciding Constitution (Article 3, subsection (1)); second, administering President and/or Vice President (Article 3, subsection (2)); and third, dismissing President and/or Vice President in the period of their position according to Constitution (Article 3, subsection (3)). Thus, MPR did not elect and administer President but it just inaugurates President. This direct Presidential election gave the effect that the President is responsible to the people directly, not to MPR. The Duty of MPR, which also decides on the GBHN, was removed because in this system the President made the programs him self, not made by MPR.